A model of the decision support system for managing the process of growing vegetables in a greenhouse - Lendiel, M.; Lendiel, T. (Energy and Automation, 2024)
The developed of automatic control systems provide constant monitoring of technological indicators in greenhouses, as well as reporting on the current state in real time and conducting analysis based on available data. Having this data in the system, the manufacturer can analyze all key indicators, their changes and impact over time and make appropriate decisions for their enterprise. However, the created systems expand over time, and accordingly the information in them also expands, so it is necessary to effectively analyze previously entered data. In this case, there is a need to create a system that will analyze indicators based on accumulated data. It is proposed to carry out analysis using OLAP and Data Mining technologies. The purpose of the research is to implement a data warehouse of a decision support system using Data Mining technology to increase the efficiency of growing vegetables in closed soil structures. In the process of developing an automated control system, a storage model of these decision support systems was developed. In the work, the structure of the dynamic database was developed using the time series algorithm. At the same time, data input, storage and analysis modules were created. The use of Data Mining technology for the analysis of large volumes of information was proposed. The obtained results of the system can be used in the process of forming management decisions for managing technological processes in the greenhouse economy. This will allow you to direct the management strategy of individual business processes in such a way as to increase the yield in greenhouses and, accordingly, the profitability of the farm as a whole. Key words: database, monitoring, Data Mining, data storage, greenhouse